Halogenated Aza-BODIPY dyes for photodynamic anticancer and antimicrobial activity studies - Magwaza, Temlandvo Matshidiso (Rhodes University, Faculty of Science, Department of Chemistry)
This thesis reports on the synthesis and characterisation of differently substituted aza-BODIPY dyes for use in photodynamic antimicrobial chemotherapy (PACT) and photodynamic therapy (PDT) activity studies. The aza-BODIPY dyes were synthesised by adding phenyl and naphthyl rings at the 3,5-positions of the aza-BODIPY core, with methylthiolphenyl (9a and 9b, respectively) or thien-2-yl rings (9c and 9d, respectively) at the 1,7-positions. 9a-c were iodinated at the 2-position to form 10a-c, respectively, while 9d was diiodinated at the 2,6-positions to form 10d. The methylthiolphenyl-substituted dyes (10a and 10b) were successfully conjugated to gold nanoparticles (AuNPs) to form nanoparticles conjugates (10a-AuNPs and 10b-AuNPs), while attempts to conjugate the thien-2-yl-substituted dyes were unsuccessful. The photophysicochemical properties of 9a-d, 10a-d and nanoconjugates 10a-AuNPs and 10b-AuNPs were investigated to determine their suitability for use in the applications. Adding heavy atoms such as iodine at the 2,6-positions of the aza-BODIPY led to enhanced singlet oxygen generation since these dyes displayed moderate to high singlet oxygen quantum yields. None of the dyes exhibited any fluorescence. The PACT activity studies for 9c-d, 10a-d, and the 10a-AuNPs and 10b-AuNPs were carried out against Staphylococcus aureus and Escherichia coli with a Thorlabs M660L3 light-emitting diode (LED) with an irradiance of 280 mW/cm2 for all dyes other than 10d. A Thorlabs M730L4 LED with an irradiance of 160 mW/cm2 was used for 10d. Time dependence studies were only carried out against Staphylococcus aureus, so very low log reductions were observed against Escherichia coli in initial concentration studies. The 10a-AuNP and 10b-AuNP nanoconjugates exhibited high antimicrobial activity with a log reduction of 9.41 and 0.00% viable colonies, while the iodinated aza-BODIPY had a log reduction of 8.94. The in vitro photodynamic therapy activities and dark cytotoxicity were investigated against human MCF-7 breast cancer cells for dyes 9c-d and 10c-d with a Thorlabs M660L3 LED (280 mW/cm2) for all dyes. The dark cytotoxicity was minimal in each case with IC50 > 50. Iodinated dyes 10c and 10d had IC50 values of 11.6 and 8.2 Î¼M, respectively, and non-iodinated dyes 9c and 9d had IC50 values of 12.5 and 19.2 Î¼M. The heavy atom effect associated with the iodine atoms increases the singlet oxygen quantum yield and enhances the suitability of the dyes for photodynamic therapy.
Keywords: BODIPY; Dyes and dyeing Chemistry; Active oxygen; Photosensitizing compounds; Photochemotherapy; Time-dependent density functional theory; Anti-infective agents